HOPELESSNESS IN J. C. DAWN'S SELECTED POEMS - Cindi Novita; Pramudana Ihsan; Ari Setyorini (Universitas Islam Sumatera Utara (UISU), 2021)
This research examines the hopelessness described in the poems by J. C. Dawn entitled Living in A Pride World, Womb, and A Soundless Tear in her book The Ripple of Existence. This research is a descriptive qualitative study that aims to describe the words used to express hopelessness. The method used to analyze the poems is the analysis of intrinsic elements in poetry with a psychological approach to find out about hopelessness experienced by the characters in each poem. Hopelessness is a condition experienced by anyone where where there is no more hope. This would also be contextualized in real life concerning the stages of someone experiencing hopelessness based on Abramson's theory. The results of the research show that the